ELEVATED SERUM GROWTH DIFFERENTIATION FACTOR 15 LEVELS IN GERIATRIC PATIENTS – SARCOPENIA AND PHYSICAL PARAMETERS. (11th November 2018) - Franz, K; Ost, M; Herpich, C; Otten, L; Coleman, V; Klaus, S; Müller-Werdan, U; Norman, K
Abstract: Chronic inflammation acts as a contributing factor in the development of age-related sarcopenia. Growth differentiation factor 15 (GDF15) is induced in various tissues due to inflammation and oxidative stress (Unsicker et al., 2013). The aim of the study was to evaluate the association between GDF15, sarcopenia and functional parameters in geriatric patients and healthy old controls. Serum GDF15 was quantified with ELISA-kits. Bioelectrical impedance analysis was used to estimate skeletal muscle mass (SM, kg) and SM-index (SMI, kg/m 2 ). Sarcopenia was defined as reduced SMI (m: ≤ 8.50 kg/m 2, w: ≤ 5.75 kg/m 2 ) (Janssen et al., 2004) and decreased gait speed over 4 meters (≤ 1.0 m/s). Knee extension strength was measured using dynamometry. Frailty was evaluated according to the Fried criteria (Fried et al., 2001) and fatigue with the validated Brief Fatigue Inventory questionnaire. In this cross-sectional study, 103 patients (76.9 ± 5.2 years, 53.4% women) and 56 healthy controls (72.9 ± 5.9 years, 57.1% women) were analyzed. Sarcopenic patients (51.4%) did not have higher GDF15 levels than non-sarcopenic patients (2.09 ± 0.25 ng/mL vs. 1.92 ± 0.15 ng/mL, p=1.00), but than healthy control subjects (0.82 ± 0.45 ng/mL, p<0.001). GDF15 correlated with gait speed (r= -0.409, p<0.001), knee extension strength (r= -0.351, p<0.001), frailty (r= 0.458, p<0.001) and fatigue (r= 0.247, p=0.003). GDF15 was significantly higher in patients than in healthy controls. Although there was no significant difference between sarcopenic and non-sarcopenic patients using established cut off values, significant associations could be found between GDF15 levels and physical parameters.